Enhancement of ginsenoside biosynthesis and secretion by Tween 80 in Panax ginseng hairy roots. (24th September 2014) - Liang, Yanlong; Wu, Jianjun; Li, Yao; Li, Jian; Ouyang, Yong; He, Zhi; Zhao, Shoujing
Abstract We evaluated the effect of Tween 80 permeabilization on ginsenoside secretion in Panax ginseng hairy roots. Tween 80 (1.2%, w/v) had no significant effect on hairy root vitality. After a 25‐day treatment with Tween 80, approximately 76% of the total ginsenosides was released into the surrounding medium. In the case of control, the ginsenosides secreted into the medium were negligible. Furthermore, when compared with control, the level of total ginsenosides was enhanced by approximately threefold under Tween treatment. Additionally, secretion of the typical ginsenoside monomers including Rb1, Rg1, and Re was analyzed, indicating that the most of them were released into the medium. Moreover, it was observed that dammarenediol synthase, a key enzyme involved in ginsenoside biosynthesis, was upregulated at both gene expression and enzyme activity levels. The expression of genes CYP716A47 and CYP716A53v2 encoding Cyt P450 enzymes catalyzing the formation of protopanaxadiol from dammarenediol and protopanaxatriol from protopanaxadiol, respectively, was slightly upregulated. These results clearly demonstrated that Tween 80 could act not only as an efficient permeabilizer to enhance ginsenoside secretion from the hairy roots, but also as an elicitor to promote the biosynthesis of ginsenoside.